2007
DOI: 10.1113/jphysiol.2007.141689
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species activate the slow force response to stretch in feline myocardium

Abstract: When the length of the myocardium is increased, a biphasic response to stretch occurs involving an initial rapid increase in force followed by a delayed slow increase called the slow force response (SFR). Confirming previous findings involving angiotensin II in the SFR, it was blunted by AT1 receptor blockade (losartan). The SFR was accompanied by an increase in reactive oxygen species (ROS) of ∼30% and in intracellular Na + concentration ([Na + ] i ) of ∼2.5 mmol l −1 over basal detected by H 2 DCFDA and SBFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
27

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(138 citation statements)
references
References 43 publications
7
103
0
27
Order By: Relevance
“…1 Myocardial stretch induces NHE1 phosphorylation at Ser703 13 through a mechanism that involves redox-induced activation of ERK1/2 and p90 RSK . 13,14 As expected, we detected a significant increase in ERK1/2 and p90 RSK phosphorylation after stretching control-injected papillary muscles, an effect that was considerably blunted in muscles from MR-silenced hearts ( Figure 5). Therefore, an activated MR is a necessary condition to induce redox-sensitive kinase activation after myocardial stretch.…”
Section: Resultssupporting
confidence: 51%
“…1 Myocardial stretch induces NHE1 phosphorylation at Ser703 13 through a mechanism that involves redox-induced activation of ERK1/2 and p90 RSK . 13,14 As expected, we detected a significant increase in ERK1/2 and p90 RSK phosphorylation after stretching control-injected papillary muscles, an effect that was considerably blunted in muscles from MR-silenced hearts ( Figure 5). Therefore, an activated MR is a necessary condition to induce redox-sensitive kinase activation after myocardial stretch.…”
Section: Resultssupporting
confidence: 51%
“…It is not known whether trout myocardium possess NHE, but our preliminary work (D. E. Warren and H.A.S., unpublished observations) suggests that, if present, it is not robust. Interestingly, a recent study has suggested a pivotal role for mitochondrial reactive oxygen species in the generation of the SFR by activation of NHE (Caldiz et al, 2007). If this is the case, the high antioxidant activity found within the trout heart, as opposed to a lack of NHE, may explain the lack of the SFR in trout ventricular tissue (Trenzado et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A second, slower, stretch-induced increase in contractility was identified in cat papillary muscle (Parmley and Chuck, 1973) and has since been observed in preparations ranging from single cardiac cells to whole hearts in a number of mammalian species (Allen and Kurihara, 1982;Alvarez et al, 1999;von Lewinski et al, 2004;Calaghan and White, 2004;Caldiz et al, 2007). This slow positive inotropic response occurs over the minutes following the initial stretch and is known as the slow force response (SFR).…”
Section: Introductionmentioning
confidence: 99%
“…29 An expanded Methods section is available in the online Data Supplement at http://hypertension.ahajournals.org.…”
Section: Measurements Of Superoxide Anion Productionmentioning
confidence: 99%